Racial Disparities in Cancer Care in the Veterans Affairs Health Care System and the Role of Site of Care - Samuel, Cleo A. (American Public Health Association, 2014)
Objectives. We assessed cancer care disparities within the Veterans Affairs (VA) health care system and whether between-hospital differences explained disparities. Methods. We linked VA cancer registry data with VA and Medicare administrative data and examined 20 cancer-related quality measures among Black and White veterans diagnosed with colorectal (n = 12 897), lung (n = 25 608), or prostate (n = 38 202) cancer from 2001 to 2004. We used logistic regression to assess racial disparities for each measure and hospital fixed-effects models to determine whether disparities were attributable to between- or within-hospital differences. Results. Compared with Whites, Blacks had lower rates of early-stage colon cancer diagnosis (adjusted odds ratio [AOR] = 0.80; 95% confidence interval [CI] = 0.72, 0.90), curative surgery for stage I, II, or III rectal cancer (AOR = 0.57; 95% CI = 0.41, 0.78), 3-year survival for colon cancer (AOR = 0.75; 95% CI = 0.62, 0.89) and rectal cancer (AOR = 0.61; 95% CI = 0.42, 0.87), curative surgery for early-stage lung cancer (AOR = 0.50; 95% CI = 0.41, 0.60), 3-dimensional conformal or intensity-modulated radiation (3-D CRT/IMRT; AOR = 0.53; 95% CI = 0.47, 0.59), and potent antiemetics for highly emetogenic chemotherapy (AOR = 0.87; 95% CI = 0.78, 0.98). Adjustment for hospital fixed-effects minimally influenced racial gaps except for 3-D CRT/IMRT (AOR = 0.75; 95% CI = 0.65, 0.87) and potent antiemetics (AOR = 0.95; 95% CI = 0.82, 1.10). Conclusions. Disparities in VA cancer care were observed for 7 of 20 measures and were primarily attributable to within-hospital differences.